Obtención y caracterización de nanocelulosa a partir de corona de piña mediante hidrólisis ácida controlada. - Ramírez Bravo, Jonathan David (My University, 2025)
In this study, nanocellulose was obtained from the pineapple crown (Ananas comosus), an agro-industrial residue with high availability and limited industrial utilization. The main objective was to evaluate the effectiveness of chemical treatment in its extraction and to characterize the resulting samples using FTIR, SEM, XRD, and statistical analysis (ANOVA) using Minitab software. The experimental protocol was structured in three phases: (1) pretreatment with 15% NaOH and bleaching with 1% NaClO to remove lignin and hemicellulose; (2) acid hydrolysis with 57% and 62% H₂SO₄ for 30 and 50 minutes; and (3) comparative analysis of the conditions. The samples obtained were coded as A1 (57%-30 min), B1 (57%-50 min), C1 (62%-30 min), and D1 (62%-50 min). FTIR analysis confirmed the removal of lignin (1739 cm⁻¹) and hemicellulose (1240 cm⁻¹), and the presence of bands characteristic of type I cellulose, including peaks at 3332, 2892, 1644, 1314, 1158, 1050, and 895 cm⁻¹. SEM revealed notable differences in morphology: sample B1 had the smallest fiber (2.22 μm), while the others showed minimum sizes of 4.44 μm. It is noteworthy that longer exposure at moderate concentrations produces more effective fragmentation. X-ray diffraction (XRD) analysis revealed that all samples retained a partially crystalline structure, with characteristic peaks at 2θ ≈ 22.5° and 15.2°, corresponding to the (200) and (110) planes of type I cellulose. The highest crystallinity index was obtained in sample B1 (57% - 50 min), which coincides with its greater fibrillar fragmentation, while sample C1 (62% - 30 min) presented the lowest value, possibly due to partial carbonization or agglomeration of amorphous phases. One-way ANOVA indicated significant differences between treatments (p = 0.012), and the Tukey test identified B1 as achieving the highest yield (71.11%) and C1 the lowest (66.67%).
En el presente estudio se obtuvo nanocelulosa a partir de la corona de piña (Ananas comosus), un residuo agroindustrial de alta disponibilidad y escaso aprovechamiento industrial. El objetivo principal fue evaluar la efectividad del tratamiento químico en su extracción, y caracterizar las muestras resultantes mediante FTIR, SEM, DRX y análisis estadístico (ANOVA) con el soporte del software Minitab. El protocolo experimental se estructuró en tres fases: (1) pretratamiento con NaOH al 15 % y blanqueamiento con NaClO al 1 % para eliminar lignina y hemicelulosa; (2) hidrólisis ácida con H₂SO₄ al 57 % y 62 %, durante 30 y 50 minutos; y (3) análisis comparativo de las condiciones. Las muestras obtenidas se codificaron como A1 (57 %-30 min), B1 (57 %-50 min), C1 (62 %-30 min) y D1 (62 %-50 min). El análisis FTIR confirmó la eliminación de lignina (1739 cm⁻¹) y hemicelulosa (1240 cm⁻¹), y la presencia de bandas características de la celulosa tipo I, incluyendo picos en 3332, 2892, 1644, 1314, 1158, 1050 y 895 cm⁻¹. En SEM, se observaron diferencias notables en la morfología: la muestra B1 presentó la fibra más pequeña (2.22 μm), mientras que las demás mostraron tamaños mínimos de 4.44 μm, destacando que mayor tiempo a concentración moderada produce una fragmentación más efectiva. El análisis por difracción de rayos X (DRX) reveló que todas las muestras conservaron una estructura parcialmente cristalina, con picos característicos a 2θ ≈ 22.5° y 15.2°, correspondientes a los planos (200) y (110) de la celulosa tipo I. El índice de cristalinidad más alto se obtuvo en la muestra B1 (57 % - 50 min), lo que coincide con su mayor fragmentación fibrilar, mientras que la muestra C1 (62 % - 30 min) presentó el valor más bajo, posiblemente debido a un efecto de carbonización parcial o aglomeración de fases amorfas. El ANOVA de un solo factor indicó diferencias significativas entre tratamientos (p = 0.012), y la prueba de Tukey identificó que B1 alcanzó el mayor rendimiento (71.11 %) y C1 el menor (66.67 %).
Keywords: SEM; FTIR; DRX; NANOCELULOSA